2006
DOI: 10.1029/2006gl027533
|View full text |Cite
|
Sign up to set email alerts
|

High resolution altimetry reveals new characteristics of the December 2004 Indian Ocean tsunami

Abstract: [1] The Indian Ocean tsunami, which occurred on December 26, 2004, was the first to be clearly observed using satellite altimeters. The wave amplitude observed in deep-ocean by TOPEX and Jason-1 was close to 60 cm about 2 hours after the earthquake. Envisat crossed the tsunami wave 3h15 after the earthquake and measured a 35 cm wave. Even though it flew over the tsunami 7h20 after the earthquake, GFO still observed a wave close to 20 cm. To better extract the tsunami signal from altimeter measurements, a speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 8 publications
2
37
0
Order By: Relevance
“…While not the focus of our study, SSH measurements allow us to identify the location of the leading edge of the tsunami. Detection of tsunamis in SSH measurements has been demonstrated in several previous studies (Okal et al, 1999;Ablain et al, 2006), although weak tsunamis generally remain obscured by background ocean variability. By utilizing satellite altimetry data, we are able to identify the location of the tsunami's leading edge in SSH measurements and test the concurrently measured σ 0 values for tsunami-induced changes in ocean surface roughness.…”
Section: Datamentioning
confidence: 72%
See 2 more Smart Citations
“…While not the focus of our study, SSH measurements allow us to identify the location of the leading edge of the tsunami. Detection of tsunamis in SSH measurements has been demonstrated in several previous studies (Okal et al, 1999;Ablain et al, 2006), although weak tsunamis generally remain obscured by background ocean variability. By utilizing satellite altimetry data, we are able to identify the location of the tsunami's leading edge in SSH measurements and test the concurrently measured σ 0 values for tsunami-induced changes in ocean surface roughness.…”
Section: Datamentioning
confidence: 72%
“…Of these four satellite altimeters, Jason-1 provides the earliest observations of the Sumatra-Andaman tsunami and has the most extensive records. Jason-1 encountered the leading edge of the tsunami 1 h 53 minutes after the earthquake (Ablain et al, 2006;Gower, 2007) at about 5°S in the Indian Ocean heading northeast on ascending pass 129 of cycle 109 (Fig. 1).…”
Section: Sumatra-andaman Tsunamimentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, by using only the cycle before the tsunami cycle, we can explore the possibility of using this simple filtering technique for real-time detection of a tsunami signal in SSH measurements. The second, more complex, filtering method is based on a specific mapping technique, first introduced by Ablain et al (2006). The method involves collecting 20 days of data before and after tsunami occurrence provided by all available altimeters (Jason-1, Jason-2, and Envisat).…”
Section: Extraction Of Tsunami Signals From Sshmentioning
confidence: 99%
“…Gower (2007) subtracted the smoothed average of SSH measured on previous and subsequent cycles to the tsunami cycle over the same pass. Ablain et al (2006) also demonstrated the utility of filtering with a more sophisticated technique based on ocean variability mapping. Both of these methods rely on measurements taken a significant amount of time after the tsunami has occurred, making them impractical to use in a real-time detection system.…”
Section: Introductionmentioning
confidence: 99%